Microstructural characterization and optimization of the ZnMg0.8(CaO)0.26 alloy processed by ball milling and subsequent extrusion - Pinc, Jan; Skolakova, Andrea; Vertat, Petr; Capek, Jaroslav; Zofkova, Zuzana; Rieszova, Lenka; Habr, Stanislav; Vojtech, Dalibor (Manufacturing Technology Journal, 2020)
Zinc is one of the most promising elements for the preparation of biodegradable metallic implants. Despite low mechanical performance for load-bearing applications, the degradation characteristics of pure zinc belong to the best from all significant biodegradable metals (Zn, Mg, Fe). The enhancement of the mechanical properties is often reached using various methods of material processing, leading to grain refinement and subsequent enhancement of the mechanical properties. In this study, the microstructure, phase composition and the possible mechanisms of intermetallic phase formation in the ZnMgCaO alloy prepared by high energy ball milling and consolidated by extrusion were studied. Formation of the Mg2Zn11, MgZn2 and CaZn13 phases during the material processing was confirmed. The creation of the phases was, with high probability, significantly affected by the magnitudes of individual components of internal energy. The increment of the internal energy led to the formation of stable Mg2Zn11 phase as well as to CaZn13 formation. Based on our results and the characterization of the microstructure, the most suitable conditions for the preparation of a ZnMgCaO alloy were found.
Keywords: Zinc; Biodegradable materials; Powder metallurgy; High energy milling; Mechanical alloying